Effective treatment of charge and spin fluctuations in dynamical and static atom-surface interactions - Romero, Marcelo Ariel (2009)
In this work we introduce a formalism that provides a good description of the correlated charge states of an atom interacting statically or dynamically with a metal surface, including realistic features of the atom-surface system. Our treatment of the Anderson impurity with an intrasite finite repulsion is based on the use of a projection operator technique and the application of the equation of motion method. The specific case of charge state configurations having zero, one, and two valence electrons of atoms with s-type valence orbital is discussed in this work. Static properties, such as the average occupation and the local density of states at the atom site and dynamical charge fractions in atom scattering processes, are compared with exact calculations and also with other existing approximations. Our treatment of the finite electronic repulsion at the atom site also reproduces satisfactorily the experimental behavior of the transmission phase shift of a dot measured by Aharonov-Bohm interferometry in both weak and strong coupling limits.